Urban-Rural Comparison of Obesity and Related_x000D_ Metabolic Disorders in Southern Turkey - (:unkn) unknown (My University, 2020)
Introduction: Once considered a high-income country problem, obesity is now on the rise in low and middle-income countries, particularly inurban settings. The aim of this study is to estimate the distribution of obesity and related metabolic morbidities between rural and urbanregions of Adana. Materials and Methods: 545 consecutive patients, applied to Pozantı State Hospital Internal Medicine outpatient clinicbetween June-September 2017 were enrolled. Diabetes mellitus and/or hypertension and/or hyperlipidemia are defined as metaboliccomorbid condition (MCC). Participants living at Pozantı were named locals, and those living in Adana city center were named springers.Results: 351 (64.4%) participants were from Pozantı and 194 (35.6%) were from Adana city center. The median Body-mass index (BMI) ofthe study population was 29.1 (17.5-48.8) kg/m2. Springers had slightly higher, but statistically insignificant BMI compared to locals (28.7kg/m2 vs. 29.6 kg/m2 respectively, p=0.078). MCC was more frequent in springers (64.4% vs 54.1%, p= 0.02). Univariate analysis revealedthat; springers (p=0.02), age>65 (p=0.00), patients with BMI>25 kg/m2 (p=0.001) and uric acid>7 mg/dl (p=0.001) is associated with MCC.Multivariate analysis displayed the association of BMI>25 kg/m2, age between 65-79 and uric acid >7 mg/dl with MCC independently.Conclusion: Obesity exists approximately one in every three cases and metabolic morbidities are observed in nearly half of the patients whoapplied to internal medicine outpatient clinic. The growing burden of obesity and related metabolic disorders in our region points to urgentpreventive strategies on a national scale.

Giriş: Bir zamanlar yüksek gelirli ülkelerin sorunu olarak görülen obezitenin, özellikle kent yaşamının yoğun olduğu düşük ve orta gelirli_x000D_ ülkelerde sıklığı giderek artmaktadır. Bu çalışmanın amacı, Adana’nın kırsal ve kentsel bölgeleri arasında obezite ve buna bağlı metabolik_x000D_ hastalıkların dağılımını belirlemektir. Materyal ve Metod: Haziran-Eylül 2017 tarihleri arasında Pozantı Devlet Hastanesi İç Hastalıkları_x000D_ polikliniğine başvuran 545 ardışık hasta dahil edildi. Diyabet, hipertansiyon ve/veya hiperlipidemi tanılarının varlığı metabolik komorbid_x000D_ durum (MKD) olarak tanımlandı. Pozantı ilçesinde yaşayan bireyler yerli, Adana şehir merkezinde yaşayan bireyler ise yaylacı olarak_x000D_ tanımlandı. Bulgular: Katılımcıların 351 (%64,4)’i Pozantı, 194 (%35,6)’ü Adana kent merkezinden idi. Çalışma popülasyonunun ortanca_x000D_ vücut-kitle indeksi (VKİ) 29,1 (17,5-48,8) kg/m2 saptandı. Yaylacılarda, yerlilere göre istatistiksel olarak anlamlı olmayan VKİ yüksekliği_x000D_ saptandı (sırasıyla 28,7 kg/m2 vs. 29,6 kg/m2, p=0,078). MKD, yaylacılarda daha sık görülmüştür (%64,4 vs. %54,1, p=0,02). Tek_x000D_ değişkenli analizler sonucunda; yaylacılarda (p=0,02), yaş>65 (p=0,00), VKİ>25 kg/m2 (p=0,001), ürik asit > 7 mg/dl (p=0,001) olanlarda_x000D_ MKD daha sık görülmüştür. Çok değişkenli analizler sonucunda ise; VKİ>25 kg/m2, 65-79 yaş arasında olmak ve ürik asit düzeyi > 7 mg/dl_x000D_ bağımsız olarak MKD varlığı ile ilişkili saptandı. Sonuç: İç Hastalıkları polikliniğine başvuran hastalardan her üç kişiden birinde obezite, ve_x000D_ her iki kişiden birinde de metabolik komorbiditeler bulunmaktadır. Bölgemizdeki artan obezite ve ilişkili metabolik problemler, ulusal_x000D_ ölçekte acil önleyici müdahale gerekliliğini ortaya koymuştur.
Güney Türkiye'de Obezite ve İlişkili Metabolik Bozuklukların Kentsel-Kırsal Karşılaştırması